2002
DOI: 10.4141/p01-180
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium inoculant and seed-applied fungicide effects on field pea production

Abstract: Field pea has been shown to benefit from the use of rhizobium inoculation and seed-applied fungicides under intensive production. The objective of this research was to determine the effect of seed- or soil-applied rhizobium (Rhizobium leguminosarum bv. viciae) inoculants and seed-applied fungicides on field pea (Pisum sativum “Carneval”) production on fields with no previous history of the crop. The study was conducted at seven locations in Saskatchewan in each of 2 yr. Fungicide treatments were Apron FL (meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
(41 reference statements)
1
15
0
1
Order By: Relevance
“…Grain yield and quality of oatÁpea intercrops have not been previously reported for Alaska. Grain yields were similar to those already published for Alberta and other temperate regions of North America (Cutforth et al, 2002;Kutcher et al, 2002;Clayton et al, 2003), and grain yields of sole cropped oat were within the ranges reported for the subarctic growing conditions of Alaska (Knight, 1994). Like crop dry matter yields, the intercropped oat and pea produced grain yields (average over combinations, 6.04 t ha (1 ), that were statistically different from sole cropped pea (average over cultivars, 3.16 t ha (1 ) but not from the sole cropped oat (average over cultivars, 5.82 t ha (1 ), and were at least numerically higher than both.…”
Section: Grain Yieldsupporting
confidence: 77%
“…Grain yield and quality of oatÁpea intercrops have not been previously reported for Alaska. Grain yields were similar to those already published for Alberta and other temperate regions of North America (Cutforth et al, 2002;Kutcher et al, 2002;Clayton et al, 2003), and grain yields of sole cropped oat were within the ranges reported for the subarctic growing conditions of Alaska (Knight, 1994). Like crop dry matter yields, the intercropped oat and pea produced grain yields (average over combinations, 6.04 t ha (1 ), that were statistically different from sole cropped pea (average over cultivars, 3.16 t ha (1 ) but not from the sole cropped oat (average over cultivars, 5.82 t ha (1 ), and were at least numerically higher than both.…”
Section: Grain Yieldsupporting
confidence: 77%
“…Soil-applied inoculant resulted in a 12% increase in seed protein concentration compared to the seed-applied inoculant. Kutcher et al (2002) indicated that there was generally a beneficial effect of inoculation on protein concentration and that granular inoculant resulted in a greater increase than liquid inoculant. There was no significant difference in protein concentration between peat inoculant and liquid inoculant.…”
Section: Seed Protein Concentrationmentioning
confidence: 99%
“…Rhizobium inoculation has shown beneficial effects on nodulation, grain yield, and protein content of peas (McKenzie et al, 2001;Kutcher et al, 2002). Rhizobium inoculation has shown beneficial effects on nodulation, grain yield, and protein content of peas (McKenzie et al, 2001;Kutcher et al, 2002).…”
Section: Rhizobium Azospirillum Azotobacter Azolla and Blue Greenmentioning
confidence: 99%